Radar-derived Surface Current Fields along RV METEOR cruise track M158 - Ruben Carrasco; Jochen Horstmann; Peter Brandt (PANGAEA, 2024)
The dataset contains near surface current fields observed between September 28, 2019, and October 22, 2019. Currents were derived from radar data acquired with a Hereon X-band marine radar (Horstmann et al., 2021). The radar was deployed on the research vessel Meteor during the research cruise M158 for the TRIATLAS project. The provided data reflects the eastward (u) and northward (v) component of the near surface current vector. The effective depth of the retrieved currents depends on the waves present (longer waves feel the current at greater depth). Here, the current data corresponds approximately to a depth between 2 m and 10 m.